1986
DOI: 10.1136/gut.27.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Doppler ultrasound measurement of superior mesenteric artery blood flow in man.

Abstract: SUMMARY A duplex scanner which consists of a real time two dimensional scanner and a pulsed Doppler flowmeter was used to measure superior mesenteric blood flow in 70 healthy subjects. By processing the Doppler shift signals, the instantaneous average Doppler shift frequency and then the instantaneous average velocity of the flow rate were calculated. Both diameter of the vessel and angle between vessel and beam were measured from real time imaging. The mean (+ standard error of the mean) of the superior mesen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(64 citation statements)
references
References 17 publications
2
60
0
2
Order By: Relevance
“…Blood flows in the superior mesenteric artery [12,13] and the right renal artery [14] were measured by transcutaneous Doppler ultrasound using a 3·5 kHz curvilinear ultrasound probe (Sonotron, Santa Clara, California, U.S.A.). The vessels were identified by ultrasound and the sample volume of the pulsed Doppler system was adjusted to the size of the vessel being interrogated.…”
Section: Regional Haemodynamicsmentioning
confidence: 99%
“…Blood flows in the superior mesenteric artery [12,13] and the right renal artery [14] were measured by transcutaneous Doppler ultrasound using a 3·5 kHz curvilinear ultrasound probe (Sonotron, Santa Clara, California, U.S.A.). The vessels were identified by ultrasound and the sample volume of the pulsed Doppler system was adjusted to the size of the vessel being interrogated.…”
Section: Regional Haemodynamicsmentioning
confidence: 99%
“…[1][2][3][4][5] Several reports have shown that enteral feeding induces a significant and progressive increase in blood flow velocity in the superior mesenteric artery that peaks 45-60 min after the meal. [6][7][8][9][10][11][12] The effect of feeding increases with the volume of milk and the interval between feedings.…”
Section: Introductionmentioning
confidence: 99%
“…Superior mesenteric artery diameter increases with a number of stimuli, including meal [37,76,90] and decreases with exercise [77], cold stimuli [81] and hypovolaemia [74]. Also SMA diameter increases in diseases with enteric manifestation [24], including Crohn's colitis [54,70] and celiac disease [1].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound (US) is cheap, easily applicable and non-invasive, yet operator-dependent [88] and prone to magnification effect and diameter overestimation [20,65,77]. Not all arteries are visualised due to their anatomic position, including CA, SMA and IMA [25,59].…”
Section: Discussionmentioning
confidence: 99%